Salivary steroids in response to ACTH: a less invasive approach to assess adrenal function in hypotensive patients with chronic renal failure - Contreras, Liliana Noemí (2006)
Summary OBJECTIVE Hypotension increases morbidity and mortality in patients with chronic renal failure .However, adrenocortical insufficiency has not been deeply investigated as possible physiopathologic mechanism of this haemodynamic dysfunction.  The aim of this study was to explore adrenocortical function through the assessment of salivary steroids after conventional ACTH-dose stimulation (rapid ACTH test) in   patients with chronic renal failure (CRF) and sustained hypotension. DESIGN Salivary samples for cortisol and aldosterone measurements were obtained in each subject before and after stimulation with ACTH (250 mg) intramuscularly injected. SUBJECTS Twenty CRF patients with sustained hypotension and twenty four healthy subjects (controls). METHODS  Salivary flow rate was calculated in each subject. Salivary cortisol and salivary aldosterone concentrations were measured at baseline and 30 minutes after ACTH intramuscular injection. RESULTS Adequate salivary function was demonstrated in each patient. Primary and secondary adrenal insufficiencies were diagnosed in two and three CRF patients, respectively. Selective hypoaldosteronism and hyperaldosteronism were found in four and  six CRF patients respectively, while normal  adrenocortical function was demonstrated in  five cases. CONCLUSIONS These data show that nine out of twenty hypotensive CRF patients had adrenocortical insufficiency (either primary or secondary) while six exhibited hyperaldosteronism as an appropriate physiological response to volume depletion. Salivary steroid measurements after rapid ACTH test offer the opportunity to less invasively investigate adrenal status in these high risk patients in which anemia and involvement of vascular access limit dynamic blood testing. Basal salivary aldosterone samples were helpful to distinguish states of aldosterone excess .